The Effect of Input and Output Targets for Routine Tasks on Creative Task Performance - Brüggen, Alexander; Feichter, Christoph; Williamson, Michael G. (The Accounting Review, 2018)
ABSTRACT In an environment where employees have the freedom to direct some time away from their day-to-day routine tasks to work on creative endeavors, we examine whether nonbinding targets for the amount of time to spend (input target) and/or the amount of output to produce (output target) on the routine task affects creative task performance. Results of a laboratory experiment demonstrate that providing both an input and an output target on the routine task leads to greater creative task performance relative to providing one or none of these targets. This result is consistent with theory suggesting that individuals need guidance as to how much routine work to complete in order to achieve the cognitive closure necessary for them to think creatively. However, individuals also need guidance that encourages them to limit time on their relatively comfortable routine work and spend time on more open-ended creative endeavors. By setting expectations as to what employees need to achieve on their more routine day-to-day responsibilities, organizations can increase the efficacy of the growing practice of allowing employees to spend a portion of their work week on creative endeavors. Data Availability: Contact the authors.